2022
DOI: 10.1097/aog.0000000000004756
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and Misoprostol for Undesired Pregnancy of Unknown Location

Abstract: For undesired pregnancy of unknown location, immediate abortion initiation with mifepristone and misoprostol is associated with more rapid exclusion of ectopic pregnancy and pregnancy termination but lower abortion efficacy than delaying for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
(27 reference statements)
2
13
1
Order By: Relevance
“…We agree with Goldberg et al that the most serious risk of initiating medication abortion for pregnancy of unknown location is delayed diagnosis and treatment of ectopic pregnancy. 1 However, significant flaws preclude the authors' conclusions and do not support the safety of immediate mifepristone in pregnancy of unknown location.…”
mentioning
confidence: 91%
“…We agree with Goldberg et al that the most serious risk of initiating medication abortion for pregnancy of unknown location is delayed diagnosis and treatment of ectopic pregnancy. 1 However, significant flaws preclude the authors' conclusions and do not support the safety of immediate mifepristone in pregnancy of unknown location.…”
mentioning
confidence: 91%
“…We commend Parker et al's original work 1 and appreciate the opportunity to respond to the Letter from him and his colleagues. In addressing the main critique, van der Schouw et al 2 studied only timing and cause of menopause and did not assess those who had oophorectomy after they had undergone menopause for any other reason.…”
mentioning
confidence: 94%
“…leading them to conclude that delaying oophorectomy to age 65 years had benefits. 1 Although van der Schouw et al did…”
mentioning
confidence: 99%
“…There is also evidence that commencing medical abortion in very early pregnancy (ie, before ultrasound visualisation of probable IUP) is safe and effective when undertaken alongside a robust protocol with close monitoring of serum-hCG levels for a satisfactory percentage decline at day 8 of abortion compared with baseline (day 1) 8–10. A systematic review conducted as part of the 2019 National Institute of Health and Care Excellence (NICE) guidelines on abortion care concluded that commencing abortion before ultrasound evidence of IUP was not associated with a significantly higher rate of missed ectopic pregnancy diagnoses 11…”
Section: Introductionmentioning
confidence: 99%